PHYSICAL EDUCATION OF UKRAINIAN SCHOOLCHILDREN DURING DISTANCE LEARNING - Sorokolit, Nataliia; Moskalenko, Nataliia; Rymar, Olha; Matviiv, Vasyl; Pasichnyk, Viktoria; Solovey, Alla; Mandiuk, Andriy; Malanchuk, Halyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article addresses the challenges associated with fostering the physical development of Ukrainian schoolchildren connected with distance learning in physical education. The primary conditions for adopting distance learning stemmed from the Covid-19 pandemic and now confronts military aggression from Russia. The goal: to track the progress of 7th-grade students' physical development through remote physical education learning programme. Research methods: theoretical analysis, literature review, pupil questionnaire, pedagogical experiments, and statistical analysis. Surveying 126 7th-grade pupils (60 boys and 66 girls) revealed a prevailing preference for traditional face-to-face physical education classes. Only 11.11% of pupils considered distance learning to replicate a well-structured physical education session. Results showed that 84.12% believed remote lessons influenced their motor activity, physical fitness, and interest in exercises, 57.15% reported decreased personal motor activity, 42.85% felt their physical fitness remained unchanged. The methods employed by teachers during distance learning included fitness programmes (58.73%), general developmental exercises (42.86%), and strength exercises (36.51%). Approximately 22.22% of pupils indicated a tendency to disengage from distance lessons. The authors’ remote physical education learning programme proved effective fitness indicators among the experimental group (EG) pupils compared to the control group (CG). Statistically significant differences were established across multiple physical fitness indicators for 7th-grade EG schoolchildren.